(untitled) (Journal Of Educational and Psychological Researches, 2017)
The research aims to know the impact of using the strategy (think-tac-toe) in the achievement of Biology subject for female students of fourth grade scientific branch. The research sample consisted of 70female students the of fourth Grade scientific Branch . The students were divide randomly, equally to two groups, experimental and control group. the two groups are equaled in the variable ( intelligence, age, previous information, former achievement of biology subject ) and the strategy applied over the entire semester. built an achievement test and it has been the expense of validity, and the reliability and The psychometric properties, and the data were analyzed statistically by recourse to Statistical package SPSS, the results showed a statistically significant difference between the experimental group female students who studied according strategy (think-tac-toe) and the control group who studied according the usual method , in achievement test for experimental group . In light of the findings conclude that the use of strategy (think- tac-toe) for female students of 4th grade scientific branch is an effect in raising the level of academic achievement . Accordingly, recommends for adoption the strategy of (think-tac-toe) in teaching, and suggests further studies to know this strategy impact on academic achievement for a various grades .